Description of Forgiveness Among Teenagers Victims of Bullying - Zabrina Rara Andini; Syafruddin Faisal Thohar (International Conference on Sustainable Health Promotion, 2025)
This study aims to determine the description of forgiveness by bullying victims in terms of three   aspects of forgiveness, namely Avoidance Motivation, Revenge Motivation, and Benevolence Motivation. There were two adolescent participants in this study who had experienced bullying in junior high school and were selected using purposive sampling. This study is a qualitative research using a phenomenological analysis method with semi-structured interviews and thematic analysis. The results show the diversity of responses and the time needed by victims to forgive the perpetrators. Additionally, this study also shows that forgiveness helps reduce negative feelings, supports psychological well-being, and contributes to post-traumatic healing, although the process differs for each individual.